Intelligent System Design Proceedings of Intelligent System Design: INDIA 2019 - Satapathy, Suresh Chandra; Bhateja, Vikrant; Janakiramaiah, B.; Chen, Yen-Wei.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2021)
This book presents a collection of high-quality, peer-reviewed research papers from the 6th International Conference on Information System Design and Intelligent Applications (INDIA 2019), held at Lendi Institute of Engineering & Technology, India, from 1 to 2 November 2019. It covers a wide range of topics in computer science and information technology, including data mining and data warehousing, high-performance computing, parallel and distributed computing, computational intelligence, soft computing, big data, cloud computing, grid computing and cognitive computing.
Acceptance of technology in the classroom: A qualitative analysis of Mathematics teachers' perceptions -- Smart Agriculture using IOT -- CSII-TSBCC:Comparative Study of IdentifyingIssues of TaskSchedulingof Bigdata in Cloud Computing -- De-Centralized Cloud Data Storage for Privacy Preserving of Data Using Fog -- MULTI LAYER PERCEPTRON BACKPROPAGATION ALGORITHM FOR PREDICTING BREAST CANCER -- IOT based Borewell Water Level Detection and Auto-Control of Submersible Pumps -- Institute Examcell Automation with Mobile Applica-tion Interface -- Plasmonic Square Ring Resonator Based Band-Stop Filter Using MIM Waveguide -- Interactive and Assistive Gloves for Post-Stroke Hand Rehabilitation.
Keywords: Computational intelligence; Engineering design; Machine learning; Electrical engineering; Computational Intelligence; Engineering Design; Machine Learning; Communications Engineering, Networks